THE EFFECT OF SMS REMINDERS AND COUNSELING ON PREGNANT WOMEN'S ADHERENCE TO CONSUMING IRON TABLETS - Gita Sekar Prihanti; Riswanda Imawan; Fauhan Yuliana Iskandar; Lucita Puspa Diastuti; Rabiatul Adawiyah; Sarah Safrillia; Swastika Dyah Permatasari; Tri Rahmat Basuki; Slavica Karajicic; Vincentas Giedraitis (Jurnal Berkala Epidemiologi, 2022)
Background: Supplementation of iron (Fe) tablets are essential to prevent pregnant women from iron deficiency anemia. Several other factors, such as knowledge, attitude, side effects, and personal access to information about iron tablet supplements, reduce the compliance of pregnant women to consume iron tablets. This study uses a combination of interventions, Short Message Service (SMS) reminders, and counseling. Purpose: This research aims to discover the effects of SMS reminders and counseling as well as factors that influence pregnant women's compliance in consuming Fe tablets. Methods: 170 pregnant women in Balowerti Public Health Center were divided into control and intervention groups. Each group received pre and post-test. The intervention group was given the treatment of SMS reminders and counseling for seven days before the post-test. The data analysis was using McNemar's paired test. Results: McNemar test results obtained the effects of the SMS Reminder and counseling on knowledge (p = 0.01), attitude (p = 0.00), and adherence (p = 0.00) of pregnant women in the intervention group as compared to the control group at the time of the post-test. The logistic regression analysis found that the factors that influence the compliance of pregnant women to consume Fe tablets (p <0.05) during the post-test comprise attitude and number of Ante Natal care (ANC). Conclusion: SMS reminders and counseling interventions improve pregnant women's adherence, knowledge, and behavior to consuming iron tablets. This result is important as a strategy to reach women's empowerment in reproductive health.